2019
DOI: 10.1108/mrr-09-2018-0367
|View full text |Cite
|
Sign up to set email alerts
|

Fighting organizational decline: a risk-based approach to organizational anti-aging

Abstract: Purpose Most mature organizations face a major decline in performance at some time during their existence. For more than three decades, it has been suggested that the management practices that could cure a troubled company could have also kept it well. Inspired by this concept, this paper is proposing a preventive approach to early implementation of turnaround strategies as an alternative for otherwise traumatic rescue efforts, further along the downward spiral. Design/methodology/approach Corporate turnarou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 77 publications
0
10
0
1
Order By: Relevance
“…According to [68], it can be summarised that the efficiency and usability of a late career depends on strategic business goals of each firm. Authors [69] mentioned that most mature organisations face a major decline in performance at some time during their existence. On the other hand, according to [59], mature employees play crucial roles in the workforce of an organisation.…”
Section: Selected Age Management Aspects Forming Competitive Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…According to [68], it can be summarised that the efficiency and usability of a late career depends on strategic business goals of each firm. Authors [69] mentioned that most mature organisations face a major decline in performance at some time during their existence. On the other hand, according to [59], mature employees play crucial roles in the workforce of an organisation.…”
Section: Selected Age Management Aspects Forming Competitive Advantagementioning
confidence: 99%
“…The study also indicated that it is also necessary to mention that ongoing education and training of mature workers are one of the most important determinants of prolonging working life. The results of [69] proposed a preventive approach to early implementation of turnaround strategies. Accordingly, they presented the model "Anti-Aging" framework that opens an opportunity for the senior management of a mature organisation to respond earlier to organisational decline and avoid the trauma associated with challenging conditions.…”
Section: Selected Age Management Aspects Forming Competitive Advantagementioning
confidence: 99%
“…En otro orden de cosas, Gotteiner, Mas-Machuca y Marimon (2019b) proponen una jerarquía de clasificaciones (etapas, estrategias y tácticas) de la investigación sobre turnaround strategies (estrategias preventivas). Siguiendo con esta línea de estudio, los autores desarrollaron otro trabajo en el que proponen una aproximación preventiva para la implementación de turnaround strategies como una alternativa a los esfuerzos de rescate que han de hacer las empresas cuando, en uno u otro momento de su trayectoria, sufren una caída en su performance (Gotteiner, Mas-Machuca, & Marimon, 2019a).…”
Section: Artículos Teóricosunclassified
“…After standard peer-review procedures over several rounds, four papers were selected for publication in this special issue. Two of these offer a holistic view of framing risk governance (Gotteiner et al, 2019;Stein et al, 2019), while the other two tackle specific issues in designing risk governance (Gleißner, 2019;Handschumacher et al, 2019). The four papers are, however, united in underpinning the relevance of risk governance choices and carry important implications for both research and practice.…”
Section: Papers Included In This Special Issuementioning
confidence: 99%